OP41 Influences of preconceptional diet on infant anthropometry: analyses from the southampton women's survey. (2nd September 2017) - Crozier, SR; Inskip, HM; Godfrey, KM; Cooper, C; Robinson, SM
Abstract : Background: Increasing evidence suggests that the pre-conceptional period is a critical time for determining future disease risk in the offspring. Maternal obesity before and during pregnancy has important consequences for offspring health, but there is limited information about the effect of pre-conceptional diet. Methods: The Southampton Women's Survey has measured the diet, body composition, physical activity and social circumstances of 12 583 non-pregnant women aged 20 to 34 years living in the city of Southampton, UK. 3158 women subsequently became pregnant and delivered liveborn singleton infants within the study period. Anthropometric measurements were taken from the babies at birth. UK-WHO z-scores were calculated for birthweight, length and head circumference. Principal component analysis of the dietary data collected before pregnancy identified a 'prudent' (healthy) dietary pattern. Using a Directed Acyclic Graph maternal education, pre-pregnancy smoking, maternal age and parity were identified as potential confounders of the association between prudent diet score and body composition at birth. In addition, analyses were adjusted for maternal height, and for sex, age and gestation where the outcome was not a z-score, to improve the precision of the model. The associations were examined using linear regression models, additionally including a term for the interaction of prudent diet score with pre-pregnancy smoking. Results: Whilst a higher prudent diet score was associated with a higher birthweight, length and triceps skinfold thickness, there were statistically significant interactions between pre-pregnancy smoking and prudent diet score for all anthropometric outcomes. Amongst women who did not smoke before pregnancy there was no association between pre-pregnancy prudent diet score and birthweight (β=−0.02 (95% CI −0.07, 0.02) SD per SD increase in prudent diet score, p=0.34) or crown-heel length (β=0.00 (-0.05, 0.04), p=0.75), whereas amongst women who did smoke before pregnancy there was a positive association between pre-pregnancy prudent diet score and birthweight (β=0.18 (0.10, 0.25), p<0.001) and crown-heel length (β=0.13 (0.07, 0.20), p<0.001). Similar interactions were found for all other neonatal anthropometric measurements. Conclusion: Women who have healthier diets before pregnancy have offspring who are larger and longer on average; this effect is much stronger amongst women who smoke before pregnancy than amongst those that don't smoke. Reduced bioavailability of key micronutrients amongst smokers points to potential mechanisms underlying this observation. This study provides further evidence that there may be benefit in developing interventions to support women to improve health-related behaviours before they become pregnant.